Friends and enemies : the Allies and neutral Ireland in the Second World War - Garner, Karen (Manchester University Press, 2021)
This history examines the fraternal friendships and embittered masculine conflicts among British, American, and Irish national leaders and their Dublin-based advisers during the Second World War, as those leaders sought to secure - or reject - Ireland's alliance with the Western Allied powers in their existential conflict with the fascist Axis powers.